SCOPE AND FINANCIAL IMPLICATIONS OF THE INTRODUCTION OF IFRS 9 USING THE EXAMPLE OF A COMMERCIAL BANK - Sławomir Juszczyk; Wioleta Bartosiak; Juliusz Juszczyk; Robert Konieczny; Bartosz Palimonka (Polityki Europejskie, Finanse i Marketing)
The aim of the research was to identify the financial consequences of introducing IFRS 9 in a leading commercial bank in Poland. The research period was six years and covered the years 2015-2020. It was established, inter alia, that IFRS 9, compared to the previously applicable IAS 39, changed the method of measuring financial assets and thus led to changes in the balance sheet and financial results. The introduction of IFRS 9 also increased financial provisions for loans to be repaid in the bank's portfolio,